Self-monitoring of blood glucose levels among pregnant individuals with gestational diabetes: a systematic review and meta-analysis - Yeh, Ping Teresa; Kennedy, Caitlin Elizabeth; Rhee, Dong Keun; Zera, Chloe; Tunçalp, Özge; Lucido, Briana; Gomez Ponce de Leon, Rodolfo; Narasimhan, Manjulaa (Frontiers in Global Women's Health, 2023)
Introduction: The World Health Organization (WHO) recommends treatment and management of gestational diabetes (GD) through lifestyle changes, including diet and exercise, and self-monitoring blood glucose (SMBG) to inform timely treatment decisions. To expand the evidence base of WHO's guideline on self-care interventions, we conducted a systematic review of SMBG among pregnant individuals with GD. Setting: Following PRISMA guidelines, we searched PubMed, CINAHL, LILACS, and EMBASE for publications through November 2020 comparing SMBG with clinic-based monitoring during antenatal care (ANC) globally. Primary and secondary outcome measures: We extracted data using standardized forms and summarized maternal and newborn findings using random effects meta-analysis in GRADE evidence tables. We also reviewed studies on values, preferences, and costs of SMBG. Results: We identified 6 studies examining SMBG compared to routine ANC care, 5 studies on values and preferences, and 1 study on costs. Nearly all were conducted in Europe and North America. Moderate-certainty evidence from 3 randomized controlled trials (RCTs) showed that SMBG as part of a package of interventions for GD treatment was associated with lower rates of preeclampsia, lower mean birthweight, fewer infants born large for gestational age, fewer infants with macrosomia, and lower rates of shoulder dystocia. There was no difference between groups in self-efficacy, preterm birth, C-section, mental health, stillbirth, or respiratory distress. No studies measured placenta previa, long-term complications, device-related issues, or social harms. Most end-users supported SMBG, motivated by health benefits, convenience, ease of use, and increased confidence. Health workers acknowledged SMBG's convenience but were wary of technical problems. One study found SMBG by pregnant individuals with insulin-dependent diabetes was associated with decreased costs for hospital admission and length of stay. Conclusion: SMBG during pregnancy is feasible and acceptable, and when combined in a package of GD interventions, is generally associated with improved maternal and neonatal health outcomes. However, research from resource-limited settings is needed.